Novel stably transfected human reporter cell line AIZ-AR as a tool for an assessment of human androgen receptor transcriptional activity - Bartonkova, Iveta; Novotna, Aneta; Dvorak, Zdenek (PloS one, 2015)
Androgen receptor plays multiple physiological and pathological roles in human organism. In the current paper, we describe construction and characterization of a novel stably transfected human reporter cell line AIZ-AR for assessment of transcriptional activity of human androgen receptor. Cell line AIZ-AR is derived from human prostate carcinoma epithelial cell line 22Rv1 that was transfected with reporter plasmid containing 3 copies of androgen response regions (ARRs) followed by a single copy of androgen response element (ARE) from the promoter region of human prostate specific antigen (PSA) gene. AIZ-AR cells remained fully functional for more than 60 days and over 25 passages in the culture and even after cryopreservation. Time-course analyses showed that AIZ-AR cells allow detection of AR ligands as soon as after 8 hours of the treatment. We performed dose-response analyses with 23 steroids in 96-well plate format. We observed activation of AR by androgens, but not by estrogens and mineralocorticoids. Some glucocorticoids and progesterone also induced luciferase, but their potencies were 2-3 orders of magnitude weaker as compared to androgens. Taken together, we have developed a rapid, sensitive, selective, high-throughput and reproducible tool for detection of human AR ligands, with potential use in pharmacological and environmental applications.
Keywords: vztah mezi dávkou a účinkem léčiva; Luciferases; buněčné klony; reportérové geny; Clone Cells; Androgen Receptor Antagonists; luciferasy; časové faktory; Cinnamates; Humans; Dihydrotestosterone; androgenní receptory; lidé; Cell Survival; antagonisté androgenních receptorů; hygromycin B; Cell Line, Tumor; Transfection; Transcription, Genetic; dihydrotestosteron; cinnamáty; genetická transkripce; Hygromycin B; Time Factors; transfekce; steroidy; Dose-Response Relationship, Drug; kryoprezervace; Cryopreservation; Steroids; Genes, Reporter; viabilita buněk; nádorové buněčné linie; Receptors, Androgen